2015
DOI: 10.1091/mbc.e14-07-1200
|View full text |Cite
|
Sign up to set email alerts
|

WAVE binds Ena/VASP for enhanced Arp2/3 complex–based actin assembly

Abstract: A dual in vitro/in vivo approach is used to show that WAVE directly binds Ena/VASP, coordinating its activity with that of the Arp2/3 complex for enhanced actin assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 74 publications
2
58
0
Order By: Relevance
“…The authors concluded that profilin antagonizes Arp2/3-mediated nucleation and actin branching by facilitating actin polymerization via Ena/VASP, thereby competing away actin monomers from the Arp2/3 complex. In contrast, Ena/VASP has also been proposed to interact with the WAVE regulatory complex to stimulate Arp2/3 activation, enhance migration, and maintain normal lamellipodia formation in Drosophila hemocytes and C. elegans epidermal cells, suggesting that this family of actin assembly proteins may have alternative functions in diverse cell types or under different conditions [106,107]. Work combining analysis of the contractile ring in S. pombe with in vitro actin reconstitution assays also shows that profilin inhibits Arp2/3 function, thereby maintaining the balance between formin- and Arp2/3-mediated actin polymerization that is required for cytokinesis [108].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that profilin antagonizes Arp2/3-mediated nucleation and actin branching by facilitating actin polymerization via Ena/VASP, thereby competing away actin monomers from the Arp2/3 complex. In contrast, Ena/VASP has also been proposed to interact with the WAVE regulatory complex to stimulate Arp2/3 activation, enhance migration, and maintain normal lamellipodia formation in Drosophila hemocytes and C. elegans epidermal cells, suggesting that this family of actin assembly proteins may have alternative functions in diverse cell types or under different conditions [106,107]. Work combining analysis of the contractile ring in S. pombe with in vitro actin reconstitution assays also shows that profilin inhibits Arp2/3 function, thereby maintaining the balance between formin- and Arp2/3-mediated actin polymerization that is required for cytokinesis [108].…”
Section: Introductionmentioning
confidence: 99%
“…So the effect of VASP on motility seems to depend on the initial state of the system, and when speed is already optimal, adding an enhancing molecule like VASP does not have the expected effect. Images taken at about 10-15 minutes reaction time of PRD-VCA-WAVE-coated beads in reconstituted motility mix as described in [65], but with Arp2/3 complex purchased from Cytoskeleton. Phase contrast microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…N-WASP is a more effective Arp2/3 complex activator than either WASP or WAVE/Scar due to the enhanced acidity of the A domain in the case of N-WASP, not as originally believed due to the extra V domain that N-WASP proteins contain [64]. WAVE/Scar-derived bead coatings have been used for some studies, but less extensively than the other NPFs [46,65]. WAVE proteins exist in regulatory complexes, which are impossible to mimic in pure protein mixtures although the WAVE regulatory complex has been successfully recruited to membrane-coated glass beads to form actin comets in cell extracts [66].…”
Section: What To Coat the Beads With?mentioning
confidence: 99%
See 1 more Smart Citation
“…The EVH1 domains target Ena/VASP proteins to sites of actin rearrangements via interactions with proteins containing the proline-rich motif (D/E)(F/L/W/Y)PPPPX(D/E)(D/E) (designated FPPPP), including zyxin and vinculin at focal adhesions and lamellipodin at the leading edge (Hoffman et al, 2006;Krause et al, 2004;Niebuhr et al, 1997). EVH1 domains also bind to diaphanous formin (Dia) and mammalian diaphanous formin 2 (mDia2), inhibiting actin nucleation and elongation (Barzik et al, 2014;Bilancia et al, 2014), and recent data suggest that VASP activates WAVE (Wiskott-Aldrich syndrome verprolin homology protein) via EVH1-mediated interactions (Chen et al, 2014;Havrylenko et al, 2015). The PRO regions bind to profilin and to SH3 and WW domain-containing proteins.…”
Section: Introductionmentioning
confidence: 99%